PSVII-17 Effects of zinc chloride supplementation during ovarian cortex vitrification prior to in vitro fertilization on embryo development in pigs. (30th November 2020) - Hicks, Emma C; Arena, Haley; Whitaker, Brian
Abstract: Ovarian tissue has an increased risk of damage during vitrification due to the presence of different cell types and water permeability levels within the tissue. Supplementation of antioxidant-like compounds such as zinc chloride improves follicular integrity and increases antral follicle development post-thawing. However, the effects of zinc chloride supplementation on the oocytes within the follicles are unknown. Therefore, the objective of this study is was to determine the effects of 5 μg/mL zinc chloride supplementation during the vitrification process on post-thawing fertilization characteristics and embryonic development. Ovarian cortex samples (5 x 5 mm; n=27) were isolated from ovaries extracted from cycling gilts. Cortical pieces were loaded onto a 25-gauge needle and incubated for five min in equilibrium solution followed by five min in vitrification solution, both supplemented with 5 μg/mL zinc chloride. Following incubation, the cortexes were place in liquid nitrogen for 7 d. Cortexes were then thawed and oocytes were aspirated from antral follicles. Oocytes (n=162) were incubated in maturation media for 40-44 h and then subjected to IVF and embryo culture. Frozen-thawed semen from three boars was used (30 oocytes/well, 200 sperm/oocyte). Post-IVF, a portion of the potential embryos (n=25) were evaluated for penetration, polyspermy, and male pronuclear formation rates. The remaining embryos (n=137) were evaluated 48 h after IVF for cleavage and 144 h for blastocyst formation. Data were analyzed using ANOVA and Tukey's test. There were no differences between treatment groups when comparing penetration, 2-cell and blastocyst formation rates. However, polyspermic penetration rates were significantly lower (P < 0.05) and male pronuclear formation were significantly higher (P < 0.05) in the zinc chloride supplemented treatment group compared to no supplementation. These results indicate that supplementing zinc chloride during ovarian cortex freezing improves fertilization characteristics of their oocytes post-thawing and maturation.